Pengaruh Penerapan Pajak Daerah, Retribusi Daerah dan Dana Bagi Hasil Terhadap Kemandirian Keuangan Daerah di Dinas Pendapatan, Pengelolaan Keuangan, dan Aset Daerah (DPPKAD) Eks Karesidenan Pekalongan Pada Tahun 2013 – 2017 - Balqis (Faculty of Economics and Business, University of Pancasakti Tegal, 2018)
The purpose of this study is 1) to determine simultaneously the effect of the application of local taxes, regional retribution and revenue sharing funds on financial independence 2) To know partially the effect of tax implementation on regional financial independence 3) To know partially the influence of regional retribution on regional financial independence 4) To know partially the effect of revenue sharing funds on regional financial independence. Data collection method used in this study is documentation. While the data analysis used is classical assumption testing, multiple linear regression analysis, simultaneous significance test (F statistical test), individual parameters significant test (t statistical test) and determination coefficient. The first hypothesis uses simultaneous parameter significance test proving that there is a positive and significant influence on the application of local taxes, regional retribution and revenue sharing on regional financial independence as evidenced by sig = 0,000 <0,05. The second hypothesis uses the individual parameter significance test proving that there is a positive and significant influence on the application of local taxes on regional financial independence as evidenced by the sig value = 0,000 <0,05. The third hypothesis uses an individual parameter significance test proving that there is a positive and insignificant influence on the regional financial independence evidenced by sig = 0.224> 0.05. The fourth hypothesis uses the individual parameter significance test proving that there is a negative and significant effect on revenue sharing on regional financial independence as evidenced by sig = 0.001 <0.05